UNDERSTANDING THE CONCEPT OF HALAL AND HALAL AWARENESS IN CONSUMER BEHAVIOR MUSLIMS IN SURABAYA (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2022)
Halal lifestyle is indeed excellent in both Muslim and non-Muslim countries. One of the industries in the global halal industry is the halal food industry. Based on data from the Global Islamic Economy Report 2018/2019, Indonesia is the highest country in terms of food at US16 billion. This research is a qualitative research with a case study approach, where the purpose of this research is to answer the problem formulation: how to understand the concept of halal Muslim consumers, how to halal awareness of Muslim consumers and how halal consumption behavior is applied by Muslim consumers. Data of this study were complied from the literature and the result of direct interviews with related research respondents, it's Muslim consumers in Surabaya, which were further analyzed by interactive analysis methods. The results of this study indicate that BreadTalk Muslim consumers understanding of the concept of halal is very good, where they understand that halal does not only lie in its substance but also includes how to obtain and process the food. For halal awareness that they have applied is good but inconsistent, where they unwittingly do not pay attention to the presence oh halal labels on the products they consume. The halal consumption behavior that they implement is consuming whatever they believe is halal. Keywords: Understanding of Halal Concepts,Halal Awareness, Halal Consumption Behavior